Exosomes modified with anti-MEK1 siRNA lead to an effective silencing of triple negative breast cancer cells - Ferreira, Débora; Santos-Pereira, Cátia; Costa, Marta; Afonso, Julieta; Yang, Sujuan; Hensel, Janine; McAndrews, Kathleen M.; Longatto-Filho, Adhemar [UNESP]; Fernandes, Rui; Melo, Joana B.; Baltazar, Fátima; Moreira, João N.; et al. (Elsevier, 2023)
Triple negative breast cancer (TNBC) is a highly heterogenous disease not sensitive to endocrine or HER2 therapy and standardized treatment regimens are still missing. Therefore, development of novel TNBC treatment approaches is of utmost relevance. Herein, the potential of MAPK/ERK downregulation by RNAi-based therapeutics in a panel of mesenchymal stem-like TNBC cell lines was uncovered. Our data revealed that suppression of one of the central nodes of this signaling pathway, MEK1, affects proliferation, migration, and invasion of TNBC cells, that may be explained by the reversion of the epithelial-mesenchymal transition phenotype, which is facilitated by the MMP-2/MMP-9 downregulation. Moreover, an exosome-based system was successfully generated for the siRNA loading (iExoMEK1). Our data suggested absence of modification of the physical properties and general integrity of the iExoMEK1 comparatively to the unmodified counterparts. Such exosome-mediated downregulation of MEK1 led to a tumor regression accompanied by a decrease of angiogenesis using the chick chorioallantoic-membrane model. Our results highlight the potential of the targeting of MAPK/ERK cascade as a promising therapeutic approach against TNBC.
Keywords: Exosome-mediated silencing; MAPK/ERK cascade; MEK1; siRNA; TNBC